TEMPLE ARCHITECTURE IN NADIA DISTRICT CONTEMPORARY TO THE KRISHNANAGAR DYNASTY: A REVIEW - Sarkar, Sujan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Nadia district, a region inhabited by rivers and canals, holds a unique place in the history of India and West Bengal. Nabadwip, in the Nadia district of West Bengal, was the capital of Bengal during the Pala and Sena periods from the 7th to the 9th century. In view of this historical importance, it is natural to have traces of temple architecture in the Nadia. But surprisingly no traces of temple architecture from 7th to 16th century can be found in Nadia. However, many temple architectures have been found in Nadia since the 17th century. In response to this discrepancy, many say that the temple architecture of Nadia was destroyed by the Muslim invasion. However, more research is needed on this. Because from the seventeenth century till King Krishnachandra, Nadia was under the rule of Muslim rulers. Many temples were built during this period. However, it is known from the writings of Srijannath Mitra Mustawfi that many temples of Nadia were destroyed by Nawab Sirajdaulah during this period. That is, during the period of the Nawabs of Murshidabad, there was a Muslim invasion in Nadia - it took a way to deny that. Despite the Muslim invasion, many contemporary temples of the Krishnanagar dynasty were established in Nadia. For example, ‘Palpara temple, ‘Krishnadev Roy’ temple of Kanchanpalli, ‘Shiva temple’ of Srinagar, ‘Dwadash (12th ) temple’ of Birnagar etc. In the construction of these temples, the traditions of the past were mostly followed. However, during the time of King Krishnachandra, Muslim and British architectural techniques were followed in the construction of the temple instead of traditional traditions. The main reason for this deviation was the financial crisis and the lack of terracotta artists. These issues are discussed in this article.